2021
DOI: 10.1186/s12992-020-00651-7
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of peer-reviewed literature on antimicrobial stewardship from 1990 to 2019

Abstract: Background The World Health Organization recommended the implementation of antimicrobial stewardship (AMS) in the clinical settings to minimize the development and spread of antimicrobial resistance (AMR). The current study aimed to assess global research activity on AMS as one measure for efforts dedicated to contain AMR. Method A bibliometric method was applied using Scopus. A validated search query was implemented. Bibliometric indicators and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(44 citation statements)
references
References 98 publications
3
39
0
2
Order By: Relevance
“…In addition, most of the social networking sites in the United States were developed and built. These results are close to earlier bibliometric studies in various fields[ 57 - 61 ], primarily because the United States has the highest activity in the worldwide development of scientific research and international cooperation networks[ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, most of the social networking sites in the United States were developed and built. These results are close to earlier bibliometric studies in various fields[ 57 - 61 ], primarily because the United States has the highest activity in the worldwide development of scientific research and international cooperation networks[ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 88%
“…Caregivers of children with DD experienced significantly higher caregiver burden, depression, anxiety and stress than those of TD children (Chafouleas & Iovino, 2020 ). In particular, parents of children with ASD reported higher levels of anxiety and depression than parents of TD children (Wang et al, 2021 ). Similarly, we adopted the DASS-21 scale to provide comparisons to baseline reported locally and across two Asian studies using similar scales.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness – a particular way of paying attention, purposefully and nonjudgmentally, to the present moment ( Kabat-Zinn, 1994 ) – is a construct that has emerged as a potential protective factor during the pandemic ( Conversano et al, 2020 ; Matiz et al, 2020 ; Sun et al, 2021 ; Zhang et al, 2021 ; Zheng et al, 2020 ). Previous research has shown reduced psychological distress among university students in Spain and China following mindfulness-based interventions designed for the pandemic ( González-García et al, 2021 ; Sun et al, 2021 ). No study, however, has thus far examined the effects of a mindfulness-based intervention on university students in the UK during the pandemic.…”
Section: Introductionmentioning
confidence: 99%